EFL students’ beliefs about AI-assisted writing and its perceived impact on their English writing development - Rika Riwayatiningsih; Raveenthiran Vivekanantharasa; Entika Fani Prastikawati (JEELS (Journal of English Education and Linguistics Studies), 2026)
Recent advancements in AI have provided new chances to support EFL writing. This study investigated the perceptions of Indonesian EFL students regarding AI-assisted writing tools and their perceived impact on English writing development. An explanatory sequential mixed-methods design was employed. A survey and asynchronous written semi-structured interviews examined students’ beliefs and perceptions regarding ChatGPT and Grammarly, the perceived impact of these tools on essential writing sub-skills, and their ethical and autonomy-related concerns within academic settings. Quantitative results showed predominantly positive perceptions, with students reporting perceived benefits for idea generation, coherence, grammatical accuracy, vocabulary choice, and overall textual clarity. Grammarly was acknowledged for improving error awareness and linguistic accuracy, whereas ChatGPT facilitated brainstorming and paragraph structuring. Interview accounts indicated cautious and critical engagement, as students reported evaluating AI suggestions rather than adopting outputs uncritically. Students also expressed concerns about misinformation, academic integrity, and the possibility of reduced confidence or independence under excessive reliance on AI-assisted feedback. Within this sample and context, findings suggest that AI-assisted writing tools may support EFL learners’ writing processes when used thoughtfully, but effective integration requires guidance that promotes ethical awareness, verification practices, and sustained writing autonomy. Future research should triangulate perceptions with  performance-based writing outcomes (e.g., rubric-scored pre–post writing tasks) and usage evidence to examine longer-term development.